The Nuisance Mosquito Anopheles plumbeus (Stephens, 1828) in Germany—A Questionnaire Survey May Help Support Surveillance and Control - Heym, Eva C.; Schröder, Jette; Kampen, Helge; Walther, Doreen (Frontiers in Public Health, 2017)
The mosquito species Anopheles plumbeus is an aggressive biter and a potential vector of malaria parasites and West Nile virus. It occurs naturally at low population densities, as its larval development is adapted to the specific water qualities found in tree-holes. However, probably owing to environmental changes, it has recently been observed in several European countries to use increasingly often artificial breeding habitats which may lead to mass development and severe annoyance to humans living close by. The perception of mosquito nuisance, however, is very subjective, and breeding habitats are not always known, thus impeding targeted surveillance and control. To relate nuisance by An. plumbeus to specific environmental conditions, a questionnaire survey was carried out addressing persons who had submitted specimens of this particular mosquito species to the German citizen science project ‘Mueckenatlas’, an instrument of passive mosquito surveillance. The questionnaire was intended to find out whether a nuisance situation linked to An. plumbeus had existed, whether mosquito breeding habitats could be identified and whether control measures had been conducted. Despite some efforts, the participants who claimed to suffer from an An. plumbeus nuisance problem had rarely identified the source of the mosquitoes. Once control measures had been performed on abandoned manure pits, however, the nuisance problem disappeared or mosquito abundance was at least significantly reduced. Nevertheless, no significant effect of abandoned manure pits on the probability of an An. plumbeus nuisance could be demonstrated in a multivariate logistic regression model testing various variables. Instead, a significant positive effect of a disused farm nearby was found. The reason is probably that manure pits as the most frequent source of An. plumbeus mass development are often located on disused farms, without most people’s knowledge about their existence. Disused farms are therefore appropriate candidates to consider when it comes to public health issues connected to An. plumbeus such as surveillance of mass development and implementation of control measures.